Mandatory disclosure in the annual reports of general insurers in Malaysia - Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (Universiti Utara Malaysia, 1998)
This research attempts to investigate the extent to which firms conducting general insurance business comply with the disclosure requirements stipulated in MAS 3(Accounting for General Insurance Business), which was issued and adopted by the Malaysian Institute of Accountants (MIA) in 1991, and the standard related to investments, namely SI 25 (Accounting for Investments). Based on the annual reports of 35 general insurers for the year 1994, the disclosure level was found to be unsatisfactory. The study further showed that insurance companies listed on the KLSE tend to have better disclosure compared with non-listed firms. Firm's size negatively influenced the level of disclosure. The size of the auditing firm, the scope of business and the number of shareholders did not influence the level of disclosure in this study.